TICs et la géographie : vers une « géographie 2.0 » ? - Jérémie Valentin (Netcom)
The history of the geography was often marked by the progress of the technical innovations. Today, after ICTs, a new Internet takes shape, the Web 2.0 which corresponds to a new approach of data processing and diffusion of the knowledge. It gives to the actor a central place in his access to the communications and information. These changes touch the society,(policy, sciences, economy, leisures…). The geography does not escape from the phenomenon. After undergohaving undergone the first changes due to the development of data processing, it is on the point of marking a new stage, under the impulse of the new software of representation of space, their tools and their facilitated broadcasting capacities.